Reno-protective and reno-restorative effect of the Epidermal Growth Factor in biomodel of Chronic Renal Failure - Carlos Rafael Núñez Cairo (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: Kidney disease is a world health problem. Epidermic Growth Factor acts as cyto-protector, and trophic restorative. Objective:  To assess the reno-protective and reno-restorative effect of the Epidermal Growth Factor in biomodel of Chronic Renal Failure. Material and Methods: 120 Wistar rats were studied in 6 groups: Negative and Positive Control, Saline Solution Single-Dose and Multiple-Dose, Epidermal Growth Factor Single-Dose and Multiple-Dose.  A single dose was applied before the damage for the reno-protective effect, and multiple doses after the damage for the reno-restorative effect, at a rate of 100 µg/kg of weight. Results: Creatinine, urea, and uric acid diminished significantly in the experimental groups, with a higher decrease for experimental group with single dose; therefore, the reno-protective effect was higher than reno-restorative one for the treatment patterns used. Conclusions:  Epidermal Growth Factor showed reno-protective and reno-restorative effect by diminishing the hematological variables in kidney damage. Keywords:  Epidermal Growth Factor, reno-protective, reno-restorative, Chronic Renal Failure, 5/6 renal ablation.